Intercultural capacity deficits: Contested geographies of coexistence in natural resource management. (6th August 2013) - Howitt, Richard; Doohan, Kim; Suchet‐Pearson, Sandie; Cross, Sherrie; Lawrence, Rebecca; Lunkapis, Gaim James; Muller, Samantha; Prout, Sarah; Veland, Siri
Abstract: Focusing on the coexistence of competing and contested interests in intercultural natural resource management (NRM) systems in Australia and Malaysia, this paper explores the ways in which ontological pluralism and the interplay of socio‐cultural, political–economic and biophysical influences shape NRM systems. We aim to foster a discursive space in which to reframe the challenges of capacity building in the rapidly changing spaces of intercultural NRM systems. The paper synthesizes the conceptual arguments of field research to conclude that capacity deficits of dominant institutions, processes and knowledge systems drive many systemic failures in land and sea management affecting Indigenous peoples. We advocate urgent action to build intercultural competence and new capacities and competencies in those institutions. The paper reframes intercultural NRM in terms of coexistence and invites wider debate about these 'new geographies of coexistence' in intercultural NRM systems.